Federalism and intergovernmental relations in strengthening of the collegiate agencies in the city of Riachuelo/RN (Research, Society and Development, 2018)
The article aims to evaluate if the interrelationship between the municipality of Riachuelo / RN and the Union through the Articulated Actions Plan provided advances in local democratic management. To do so, the following indicators will be analyzed: School councils (CE) and the Municipal Council of Education (CME) in the PAR of the municipality from the periods of 2007 to 2011 and 2011 and 2014. The procedures adopted were: literature review, documentary and semi-structured interviews with members of the local technical team to elaborate the Riachuelo PAIR. The results show that Brazilian federalism and the intergovernmental relations established in it show asymmetries, thus compromising the implementation of the federative pact in Brazil. The interrelationship between the Union and the municipality in the development of educational public policies provided for in the Articulated Action Plan of Riachuelo, both in 2007 and in 2011, were not enough to consolidate democratic management in the municipal education system. This management model, however, is something to be constructed procedurally. The challenge of democratizing school and educational management is a task that is not exhausted in the execution of educational policies, especially on time. Democratizing management implies, therefore, to rethink the structures of power not only in the school, but in the whole society.